Influência do tempo de exposição ao meio ambiente, da desinfecção química e da pigmentação sobre a estabilidade dimensional e a manutenção da reprodução de detalhes de silicones nacionais para uso em prótese facial - Guiotti, Aimée Maria [UNESP] (2003)
The purpose of this study was to analyse the influence of time exposure to the environmental factors, chemical disinfection with 2% chlorhexidine-based solution and two distincts pigments about dimensional changing and maintenance of details of two silicones for use in maxillofacial prosthesis. Thirty specimens were fabricated for each silicone using a matrix, conformed closely to the specifications for nonaqueous, elastomeric dental impression materials established by the Revised American Dental Association n° 19 and the ISO 4823:1984. Specimens were separated in three groups: control (colourless), pigmented with commercial cosmetic (makeup powders) and pigmented with iron oxid. Specimens were analysed in a comparator microscopic (Carl Zeiss) and stereoscopic loupe. The readings were realized after polymerization of the specimens, and after 30 and 60 days, with and 157 without disinfection. The data were submited to the statistic analysis, by the Tukey’s Test. The results indicated that all groups presented contraction; the chemical disinfection only changed the dimensional stability of the Silastic cosmetic pigmented group; the dimensional stability of Silastic was affected after 60 days of exposition in all groups. For the Brascoved silicone, the chemical disinfection only didn´t have influence about dimensional stability in initial period; the exposition factor had influence about the dimensional stability of Brascoved in all periods and groups. The details were maintained in all specimens for both silicones, independent of the exposition time, of the pigments or disinfection.